Narcissism and lack of interpersonal forgiveness: The mediating role of state anger, state rumination, and state empathy. (March 2015) - Fatfouta, Ramzi; Gerlach, Tanja M.; Schröder-Abé, Michela; Merkl, Angela
Highlights: Examined relations between narcissistic rivalry/admiration and unforgiveness ( N  = 1040). Anger, rumination, and empathy for the transgressor acted as mediators. Higher empathy for the transgressor emerged as a mediator in admiration. Higher anger/rumination and lower empathy were mediators in rivalry. Abstract: The present study investigated the unique contributions of two distinct dimensions of narcissism – admiration and rivalry – to two facets of unforgiveness: revenge and avoidance. In addition, we examined whether state anger, state rumination, and state empathy mediate this relationship. Using a large sample ( N  = 1040), we found that admiration was negatively related to revenge and avoidance via higher empathy for the transgressor. By contrast, rivalry was positively related to revenge and avoidance via greater anger and rumination and less empathy. Findings suggest that the mechanisms through which narcissism and lack of forgiveness are associated are better understood if we disentangle admiration and rivalry and consider both cognitive and affective antecedents of narcissists' unforgiving motivations.